Implementasi Ecobrick dalam Mendukung Kebersihan dan Daya Tarik Wisata Medan Bapaneh Sawahlunto - Septri .; Hidayatul Akbar; Helvi Kurnia Ilahi; M.Radit Al Fauza; Muhamad Ifdal; Anggun Oktavia; Fharid M. Febrizan; Mutiara Putri Ayu; Shinta Trisa Andesto; Waldan Shakir Zulfayri (CV. ITTC INDONESIA, 2026)
This study discusses the limited academic documentation of the Jami Jobang folklore as part of the randai tradition in Bukik Gadang, Talawi, Sawahlunto. The purpose of this study is to describe the history and content of the Jami Jobang story, analyze its transformation into randai performance, and identify the cultural values contained in the story. This study used a descriptive-participatory method through manuscript study, field observation, documentation, and visits to a burial site related to the Jami Jobang story. The data were analyzed descriptively by identifying cultural themes, story structure, character roles, traditional values, moral values, social values, and elements of randai performance. The results show that Jami Jobang is part of the collective memory of the Talawi community and contains adat, moral, religious, social, educational, and preservation values. The randai script includes important performance elements such as galombang anak randai, dendang, dialogue, and legaran. This study also shows that KKN students can actively contribute to local cultural preservation through documentation, manuscript study, field observation, and strengthening community cultural literacy.